PENGEMBANGAN BUKU SAKU MATERI MAMALIA DI TAMAN MARGASATWA RAGUNAN UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA - Muhamad Taufik Awaludin; R. Teti Rostikawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
This study aims to develop a pocket book in learning biology in order to increase students enthusiasm for learning and is an effort to improve students mastery of concepts. The research was carried out on class X high school students. Data collection was carried out at Ragunan Wildlife Park, Jakarta. The research was carried out in the even semester of the 2019/2020 school year, January to June 2020. The method used in this study was the research and development method using the 4-D (Four D) model, namely Define, Design (Design). , Develop (Development), and Disseminate (Spread). The development of teaching materials is carried out in two stages, namely: Expert Validation and Revision of Learning Media. Based on the results of the study, it can be concluded that the pocket book Mammals of the Primate order which was developed with the define, design, develop stage has met the components that are in accordance with KD in the 2013 curriculum, the language used is easy to understand, the presentation of a pocket book that is full of color and the images shown are very supportive of the material. learning so that it can attract the readers attention. The Primate Order Mammals pocket book shows valid results and is suitable for use in biology learning. The average value of expert validation from the content / content aspect was 83.5 percent, the language aspect was 83 percent, and the presentation aspect was 82.5 percent.